(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study is of great importance in clarifying the reality of enterprise risk management procedures in major Saudi companies and evaluating their effectiveness in achieving objectives. Risk management is essential for the performance and sustainability of any organization, especially in the dynamic and complex business world characterized by escalating and diverse risks. This research enhances the theoretical and practical understanding of enterprise risk management systems and provides practical solutions to increase their effectiveness in Saudi companies. The research also facilitates a deeper understanding of the application of enterprise risk management systems in the specific context of the Saudi market, thus increasing companies’ ability to confront problems and achieve their strategic objectives. This study seeks to evaluate the effectiveness of enterprise risk management systems in major Saudi companies. This includes evaluating the clarity of the system’s objectives, employees’ awareness of its importance, the degree of its integration with organizational processes, the adequacy of allocated resources, and its contribution to enhancing the decision-making process, mitigating risks, and enhancing the organization’s reputation. The study aims to evaluate the extent of senior management’s involvement in supporting, implementing, and evaluating risk management systems. The study used the descriptive analytical approach, benefiting from data collected through a questionnaire applied to a sample of 160 major Saudi companies. The data were examined using descriptive statistical techniques, including standard deviation and skewness, to illustrate the characteristics and distribution of the data. The results showed that the enterprise risk management systems in Saudi companies have a reasonable level of effectiveness, with global agreement on their importance and benefits. The results also showed that there is a focus on providing training and enhancing knowledge of the need for risk management among employees, and that most organizations use advanced techniques and procedures to control risks. The results indicated that senior management is committed to supporting and following up on the adoption of risk management systems, and actively participates in reviewing their performance. The results also showed that companies seek to continuously improve their risk management systems through periodic evaluation and learning from previous experiences.